Immunopathology of intraocular silicone oil: enucleated eyes. Issue 2 (27th September 2006) - Wickham, Louisa; Asaria, Riaz H; Alexander, Robert; Luthert, Phil; Charteris, David G
Abstract : Aims: To characterise the distribution of silicone oil in ocular tissues in globes enucleated after complicated retinal detachment, and to document the distribution and nature of any associated inflammatory response. Method: 9 enucleated globes that had previously undergone retinal detachment surgery with silicone oil and 7 control globes that had undergone enucleation after retinal detachment surgery (n = 2) or ocular trauma (n = 5) were studied. Sections were histologically examined using light microscopy to document the distribution of silicone oil in ocular tissues. Immunohistochemical analysis was carried out using the ABC technique and a panel of monoclonal and polyclonal antibodies. Electron microscopy was undertaken to observe the penetration of silicone oil in the trabecular meshwork of the anterior chamber drainage angle. Results: Silicone oil was distributed throughout the globes—notably in the iris, ciliary body, retina, trabecular meshwork and epiretinal membranes. Focal areas of intraretinal silicone were associated with disorganised retinal architecture, retinectomy sites or subretinal oil. The distribution of macrophages was closely related to the distribution of silicone oil. T and B lymphocytes were not associated with silicone oil unless additional pathology was also present—for example, cyclitic membrane or uveitis. One of the nine eyes had silicone oil present in the optic nerve. In the control globes, the inflammatory response was mediated primarily by macrophages and T lymphocytes, and was less marked than that observed in the silicone oil globes. Conclusion: This study shows that silicone oil may be sequestered in varied ocular tissues and is associated with localised inflammation mediated by macrophages.